2014
DOI: 10.1111/jce.12550
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐Based Electromagnetic Navigation to Facilitate Implantation of Left Ventricular Leads in Cardiac Resynchronization Therapy

Abstract: Use of the new navigation system enables safe and successful LV lead placement with improved orientation and significantly reduced radiation exposure during CRT implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Interestingly, despite being a novel technology and skill-set, a non-significant trend toward shorter procedure duration was observed (120 vs. 138 minutes with non-MDG, P = 0.088). Similar results were noted in the series by Doring et al, where using a matched comparison with conventional CRT device implantations the authors demonstrated a significant reduction in fluoroscopy time (median 8.0 vs. 4.5 minutes; P = 0.016) and radiation dose (median 603-338 cGy.cm 2 , P = 0.044) [12].…”
Section: Device Implantssupporting
confidence: 73%
“…Interestingly, despite being a novel technology and skill-set, a non-significant trend toward shorter procedure duration was observed (120 vs. 138 minutes with non-MDG, P = 0.088). Similar results were noted in the series by Doring et al, where using a matched comparison with conventional CRT device implantations the authors demonstrated a significant reduction in fluoroscopy time (median 8.0 vs. 4.5 minutes; P = 0.016) and radiation dose (median 603-338 cGy.cm 2 , P = 0.044) [12].…”
Section: Device Implantssupporting
confidence: 73%
“…In the setting of device implantations, EAMS have been used to reduce radiation dose particularly in children and pregnant women . Recently, the first experiences of CRT devices implantation guided by EAMS have been published . The preliminary findings of these studies indicated that this approach significantly reduces radiation exposure and may even allow fluoroscopy to be completely avoided .…”
Section: Discussionmentioning
confidence: 99%
“…Median procedural time was 140 (122-180) minutes (average 158 minutes) and did not significantly differ compared with EAMS-guided procedures (P = 0.13). Coronary sinus angiography rate (83%) and median fluoroscopy time (median 16 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] minutes, average 20 minutes, mean DAP 88114 cGy*cm 2 ) were significantly higher than EAMS-guided procedures (P < 0.001 and P < 0.001, respectively). The LV lead was successfully implanted in 242 (97%) patients and complications were observed in 17 (7%) including CS dissection (N = 7), dislodgment of the atrial (N = 1) or LV lead (N = 4) requiring repositioning, pocket hematoma (N = 2), pocket infection (N = 1), and acute kidney failure (N = 2).…”
Section: Comparison Between Eams-guided and Traditional Crt-implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, such EAMs are not routinely used during pacemaker implantation. However, some experiences with pacemakers and defibrillators in adults have been reported, in a grown‐up congenital heart defect (CHD) patient and in pediatric patients . In children with complete atrioventricular block (CAVB), the endocardial pacing site is often the right ventricular (RV) apex (RVA), although alternative RV sites (RVAPS) have been proposed to prevent or reduce RV pacing‐induced left ventricular (LV) dysfunction .…”
Section: Introductionmentioning
confidence: 99%